2020
DOI: 10.4236/jss.2020.89011
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Contemporary Communication Technology on Undergraduate Students’ Dating Violence Episodes: An Exploration of Routine Activity Theory

Abstract: The study was an empirical exploration of the kinds of communication technologies used in perpetrating different forms of Cyber Dating Abuse. The study was guided by Routine activities theory which states that the daily activities that individuals engage in make them susceptible to Cyber Dating Abuse. The study utilized data collected from 315 dating undergraduate students from selected universities in Nairobi City County, Kenya. The research design used in the study was a cross-sectional descriptive survey. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similarly to this finding, Picard (2007) detected that 30% of 382 participants received ten or more SMSs in an hour from their partners to locate or stalk them; 25% were harassed or humiliated through text messaging (SMS), and 22% was forced to have sexual intercourse. Mayoyo, Ogeno & Likoye (2020) conducted a study with university students and found common stalking and controlling behaviors via cell phone; 64% of the participants reported that they were oppressed to reply swiftly to phone calls and text messages. Thus, it can be concluded that making a phone call or sending each other text messages when not together are normal behaviors, which may become cyber dating violence when repeated annoyingly for one partner.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to this finding, Picard (2007) detected that 30% of 382 participants received ten or more SMSs in an hour from their partners to locate or stalk them; 25% were harassed or humiliated through text messaging (SMS), and 22% was forced to have sexual intercourse. Mayoyo, Ogeno & Likoye (2020) conducted a study with university students and found common stalking and controlling behaviors via cell phone; 64% of the participants reported that they were oppressed to reply swiftly to phone calls and text messages. Thus, it can be concluded that making a phone call or sending each other text messages when not together are normal behaviors, which may become cyber dating violence when repeated annoyingly for one partner.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of Dating Violence Open Journal of Social Sciences more informal sources, namely friends, parents, and family (Adams & Williams, 2011a;Mayoyo, Ogeno, & Likoye 2020;Weisz & Black, 2009). Conversely, teachers are most often mentioned with regard to requests for help from formal sources.…”
Section: State Of Knowledge About the Request For Help Andmentioning
confidence: 99%
“…Other barriers that inhibit adolescents from seeking help include: the adolescents' lack of knowledge of the existing services (Mayoyo, Ogeno, & Likoye 2020;Sabina et al, 2014), an inadequate intervention for adolescents, and the lack of screening protocols (e.g., in schools) (Moore, Sargenton, Ferranti, & Gonzalez-Guarda, 2015). The attitudes of teachers or school personnel, who do not consider DV to be a serious problem in adolescence and who believe that preventing it is not their responsibility, is another possible obstacle (Khubchandani, Price, Thompson, Dake, Wiblishauser, & Telijohann, 2012;Sundaram, 2016).…”
Section: State Of Knowledge About the Request For Help Andmentioning
confidence: 99%